Gastronomia e turismo: panificação tradicional em São Gotardo, Caxias do Sul-RS, Brasil./Gastronomy and tourism: Traditional breadmaking in São Gotardo, Caxias do Sul-RS, Brazil - Etiene Meyer Johannsen; Susana de Araujo Gastal; Ana Maria Costa Beber (Geografares, 2018)
In the final decades of the nineteenth century, immigrants from Italy arrived at southern Brazil in search of new perspectives of life. Among culinary traditions brought by them are ways of baking, since bread is a culturally important food in the ways of life of this and other ethnic groups. Considering this context, present article proposes to register traditional processes of baking in São Gotardo, Caxias do Sul, Brazil, where Italian-descendants still use clay oven and non-industrial yeasts. It’s important to consider that São Gotardo is located in the tourist region of the Serra Gaucha, and gastronomic offer can turn out to be a differential in the dispute to attract tourists to this place. Methodology was supported by participant observation, with interview, photographic record and notes in research diary, as well as baking workshops for demonstration and registration of recipes and bread preparation techniques, attended by four old women from the community who still produce the yeast itself, for use in domestic baking. As a result, it is possible to note that there is permanence of traditions associated with the eating habits of Italian-Brazilian families of São Gotardo, through making of bread with potato and apple yeast, and the rituals that surround it. In this way, it is understood that the material and symbolic patrimony present in bread can constitute a product of tourist consumption based on the local gastronomic identity.